2019
DOI: 10.1111/ases.12743
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dementia on surgical outcomes of laparoscopic cholecystectomy for symptomatic cholelithiasis and acute cholecystitis: A retrospective study

Abstract: IntroductionThe aim of this study was to clarify the impact of dementia on surgical outcomes of laparoscopic cholecystectomy for symptomatic cholelithiasis and acute cholecystitis.MethodsWe reviewed medical data of 96 patients who underwent laparoscopic cholecystectomy for symptomatic cholecystitis and acute cholecystitis. The patients were divided into the dementia group (n = 18) and non‐dementia group (n = 78). Clinical features of the patients and surgical outcomes were compared between the two groups.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Laparoscopic cholecystectomy (LC) was conducted for the first time in 1987, [ 1 ] and it is now a successful surgical method to treat the biliary colic, cholecystitis, and cholelithiasis. [ 2 – 4 ] The popularization rate of LC is getting higher and higher, which is mainly because the surgical scars left by laparoscopic surgeries is very small; it only needs a short hospital stay, and can promote the early recovery. Compared with the traditional open surgeries, LC improves the outcome and is regarded as the standard-of-care of the cholecystitis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LC) was conducted for the first time in 1987, [ 1 ] and it is now a successful surgical method to treat the biliary colic, cholecystitis, and cholelithiasis. [ 2 – 4 ] The popularization rate of LC is getting higher and higher, which is mainly because the surgical scars left by laparoscopic surgeries is very small; it only needs a short hospital stay, and can promote the early recovery. Compared with the traditional open surgeries, LC improves the outcome and is regarded as the standard-of-care of the cholecystitis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] For instance, Ninomiya and colleagues analyzed patients undergoing laparoscopic cholecystectomy and found no differences in mortality based on dementia status. 15 Bekelis et al reported on nearly 350,000 patients undergoing a broad range of cardiac, neurosurgical, and vascular operations and similarly found no association between dementia and mortality. 4 In contrast, the present study found dementia to be associated with increased odds of in-hospital mortality following all included emergency general surgery procedures except repair of perforated ulcer.…”
Section: Discussionmentioning
confidence: 99%